Plant Growth-Promoting Rhizobacteria as Tools to Improve the Growth of Kohlrabi (Brassica oleracea var. gongylodes) Plants in an Aquaponics System - María Carmen Piñero; Jacinta Collado-González; Ginés Otálora; Josefa López-Marín; Francisco M. del Amor (Plants, 2024)
The use of nitrogen as a fertilizer can be highly risky when used excessively, and it is therefore necessary to find novel techniques to reduce its use. Aquaponics reduces the use of synthetic fertilizers and water, and the leaching of nitrate into the environment. One way to avoid problems due to a reduction in nitrogen availability could be the use of plant growth promoting rhizobacteria (PGPR). This study examines the effect of PGPR on kohlrabi plants grown with a traditional nutrient solution (100S), in combination with “fish water” (50F/50D), or with a supplement of synthetic fertilizers (50F/50D + S). Two formulations were used: T1 (Azospirillum brasilense and Pantoea dispersa) and T2 (Azotobacter salinestris). Irrigation with 50F/50D caused a reduction in several of the measured parameters. The combined application of 50F/50D with T1 attenuated the negative effects. T2 did not present significant effects on the parameters measured. The results obtained with 50F/50D + S hardly showed differences with the 100S. Thus, by irrigating with 50F/50D + S, we were able to maintain the yields while reducing fertilizer use and water. The combined use of T1 and 50F/50D was also positive; however, it would be necessary to continue adjusting the amount of nitrate supplied to maintain production.